Pengembangan E-modul Elemen Praktik Dasar Memasak secara Menyeluruh pada Materi Bahan Makanan untuk Sekolah Menengah Kejuruan Program Keahlian Kuliner - Anggini, Nurul; Artanti, Guspri Devi; Kandriasari, Annis (Peneliti.net, 2024)
This research study aims to develop and test the feasibility of e-modul teaching materials for food ingredients in the subject of basic culinary. This research was conducted at SMK Negeri 4 Kota Jambi in the Culinary Skills Program. The method used is research and development (R&D) with the Borg and Gall development model consisting of stages 1) research and information collecting, 2) planning, 3) develop preliminary form a product, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing, 9) final product revision, and 10) dissemination and implementation. Techniques of data analysis in this research and development are quantitative and qualitative. The result of validation test from initial field testing through one to one test by experts obtained result of 93.3% for the instructional design aspect 91% for the material aspect 97.9% for the media aspect 88.9% for the language aspect, and the results of the one to one test by learners obtained obtained result of 93.1%. The results of the feasibility test obtained 91.1% for the small group test and 90.7% for the field group test. Based on the test results, it can be concluded that the development of e-module on element of basic cooking practices as a whole on food ingredients material are categorized as very suitable for use in the learning process. The resulting e-modules can help learners in understanding food ingredients independently, effectively and pleasantly.